Performance of Ge and In0.53Ga0.47as thermophotovoltaic cells under different spectral irradiances - Gamel M.M.A.; Ker P.J.; Rashid W.E.S.W.A.; Lee H.J.; Hannan M.A.; Jamaludin M.Z.B. (Institute of Electrical and Electronics Engineers Inc., 2023)
Antireflection coatings; Cells; Computer software; Efficiency; Energy gap; Gallium alloys; Gallium arsenide; III-V semiconductors; Indium alloys; Open circuit voltage; Photoelectrochemical cells; Photovoltaic cells; Photovoltaic effects; Reflective coatings; Semiconducting germanium; Semiconducting indium; Semiconducting indium gallium arsenide; Semiconductor alloys; Average efficiencies; Blackbody temperatures; Illumination intensity; Indium gallium arsenide; Infrared illumination; Performance parameters; Thermophoto voltaic cells; Thermophotovoltaic systems; Cytology